Preparation method and application of metal monatomic carbon-based catalyst for in-situ growth of carbon nanotubes

By growing carbon nanotubes in situ in ZIF8-M nanoparticles to form a bridged structure carbon-based catalyst and achieve high-density metal single atom distribution, the problem of low mass transport and charge transfer efficiency of ZIF carbon materials in electrochemical reactions is solved. , significantly improving the activity and efficiency of the catalyst, making it suitable for large-scale production.

CN119361731APending Publication Date: 2025-01-24KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411488908.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing ZIF carbon materials have low efficiency in electrochemical reactions, and the carbon nanotube bridged structure prepared by pyrolysis has problems of gasification loss and reduced active sites.

Method used

Prepare ZIF8-M nanoparticles by controlling the types and quantities of transition metal doping, and directly prepare carbon nanopase to grow in situ in the control of thermal solution temperature, time, and atmosphere. Distributed with high -density metal single atoms on the surface of carbon nanotubes.

Benefits of technology

It has significantly improved the reaction activity point and charge transfer efficiency of the catalyst, promoted the activity of the oxygen reaction (ORR), reduced the cost of catalyst, and was suitable for large -scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361731A_ABST
    Figure CN119361731A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a metal monatomic carbon-based catalyst for in-situ growth of carbon nanotubes. The preparation method comprises the following steps: (1) dissolving dimethylimidazole in methanol to obtain a solution A; (2) dissolving transition metal salt and zincate in methanol to form a solution B; (3) mixing the solution A and the solution B to prepare a precursor; and (4) carrying out heat treatment on the precursor at 900-1100 DEG C in the presence of mixed gas of inert gas and H2 to obtain the metal monatomic carbon-based catalyst for in-situ growth of the carbon nanotubes. According to the invention, while the reaction active sites of the catalyst are increased, a bridging structure formed by mutual crosslinking of the carbon nanotubes effectively improves the material transport and charge transfer efficiency in the reaction process, and promotes the significant improvement of the ORR intrinsic activity of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the preparation technology and application field of catalytic materials, and in particular to a preparation method and application of a metal single-atom carbon-based catalyst for in-situ growth of carbon nanotubes. Background Art

[0002] Due to the excessive exploitation of fossil energy, the energy shortage problem is becoming increasingly serious, and it is imperative to develop a clean and efficient renewable energy system. Fuel cells, as an efficient, economical and environmentally friendly new energy conversion device, have received much attention. However, fuel cell catalysts mainly rely on Pt-based catalysts. The scarcity and high price of Pt resources make the catalyst cost high, which hinders the commercialization of fuel cells. Therefore, finding non-precious metal catalytic materials that are abundant in earth resources and low in price as catalysts and reducing the cost of catalysts have become the key to promoting the commercialization of fuel cells.

[0003] In recent years, carbon materials prepared by pyrolysis of zeolitic imidazolate frameworks (ZIFs) coordinated by transition metal ions and organic imidazolates have the characteristics of high stability and high porosity, and have attracted widespread attention in many fields such as electrocatalysis, energy conversion and storage devices. However, although the carbon particles formed by pyrolysis can maintain good morphology and uniform size, the individual particles are relatively isolated, and the material transport and charge transfer efficiency during the electrochemical reaction is low. In order to solve this problem, some researchers currently connect ZIFs particles by incorporating commercial carbon nanotubes during the synthesis of ZIFs, and then achieve bridging between carbon particles through high-temperature pyrolysis to achieve the purpose of improving the material transport and charge transfer efficiency of the catalyst. However, during the high-temperature pyrolysis of ZIFs, the added carbon nanotubes will be lost in large quantities due to long-term high temperature, which fails to achieve the ideal bridging effect and causes unnecessary cost increase. On the other hand, the residual carbon nanotubes continue to gasify due to high temperature, and it is difficult for the metal atoms with catalytic activity to form a stable structure on their surface and attach, resulting in a reduction in active sites. Summary of the invention

[0004] In view of the problems of low material transmission and conductivity efficiency of current ZIF carbon materials and the difficulties in preparing bridged structures, the present invention prepares transition metal-doped ZIF8-M nanoparticles by controlling the type and amount of transition metal doping, and then directly prepares carbon nanotubes by in-situ growth to obtain a bridged structure carbon-based catalyst by controlling factors and methods such as pyrolysis temperature, time and atmosphere, and simultaneously achieves high-density metal single atom distribution on the surface of the carbon matrix and carbon nanotubes, increasing the reaction active points of the catalyst, and the bridged structure formed by cross-linking of carbon nanotubes effectively improves the material transmission and charge transfer efficiency during the reaction, thereby promoting a significant improvement in the ORR intrinsic activity of the catalyst.

[0005] The present invention provides a method for preparing a metal single-atom carbon-based catalyst for in-situ growth of carbon nanotubes, comprising the following steps:

[0006] (1) dissolving dimethylimidazole in methanol to obtain solution A;

[0007] (2) dissolving a transition metal salt and a zincate in methanol to form a solution B;

[0008] (3) The solution A and the solution B are mixed to obtain a precursor;

[0009] (4) The precursor is heated in an inert gas and H 2 The metal single-atom carbon-based catalyst for in-situ growth of carbon nanotubes is obtained by heat treatment at 900-1100° C. under mixed gas.

[0010] In the present invention, the transition metal salt is at least one of nitrates, acetates, chlorides or sulfates of cobalt, iron, manganese, nickel or molybdenum.

[0011] In some specific embodiments of the present invention, the transition metal salt is at least one of ferrous sulfate heptahydrate, ferric chloride hexahydrate, ferric acetylacetonate, and ferric nitrate nonahydrate;

[0012] In some specific embodiments of the present invention, the transition metal salt is ferrous sulfate heptahydrate.

[0013] In some specific embodiments of the present invention, the zincate is any one of zinc nitrate or zinc acetate.

[0014] In some specific embodiments of the present invention, the molar ratio of zincate to transition metal salt is 20:1-3.

[0015] In some specific embodiments of the present invention, the reaction temperature of step (3) is 10-30°C.

[0016] In some specific embodiments of the present invention, in step (3), washing is also performed with an ethanol-water mixed solution, and the ethanol concentration is 65% to 85%.

[0017] In some specific embodiments of the present invention, the heat treatment time in step (4) is 1 to 4 hours.

[0018] In some specific embodiments of the present invention, the inert gas in step (4) is Ar and / or N 2 .

[0019] In some specific embodiments of the present invention, the inert gas and H 2 The volume ratio is 100:2~10.

[0020] The present invention provides a metal single-atom carbon-based catalyst for in-situ growth of carbon nanotubes. The catalyst is obtained by the above-mentioned preparation method.

[0021] The present invention also provides applications of the catalyst obtained by the above-mentioned preparation method in the fields of electrocatalysis, fuel cells and metal-air batteries.

[0022] Compared with the prior art, the beneficial effects of the present invention are:

[0023] (1) The present invention prepares carbon nanotubes by a one-step pyrolysis method to in-situ grow bridged carbon-based catalysts ZIF8-M@CNTs, and simultaneously realizes high-density metal single atom distribution on the carbon matrix and the surface of carbon nanotubes. While increasing the reaction active points of the catalyst, the bridged structure formed by cross-linking carbon nanotubes effectively improves the material transfer and charge transfer efficiency during the reaction, and promotes a significant improvement in the intrinsic activity of the catalyst ORR;

[0024] (2) The present invention prepares high-performance, bridged ZIF8-M@CNTs catalysts by one-step pyrolysis, which has a good cost-reduction and efficiency-enhancing effect compared with the traditional method of adding commercial carbon nanotubes;

[0025] (3) The raw materials used in the present invention are cheap and easily available, the preparation process is simple, the equipment requirements are low, and the yield is high, which is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The SEM comparison images of the ZIF carbon-based catalysts of Example 1 and Comparative Example 1;

[0027] Figure 2 is the TEM image of Example 1;

[0028] Figure 3 is the HR-TEM image of Example 1;

[0029] Figure 4 is the HAADF-STEM image of Example 1;

[0030] Figure 5 It is a comparison diagram of LSV curves of the catalyst obtained in Example 1, the catalyst obtained in Comparative Example 1 and commercial Pt / C (20 wt.%) in 0.1M KOH solution;

[0031] Figure 6 is the LSV curve of Example 2 in 0.1M KOH solution;

[0032] Figure 7 is the LSV curve of Example 3 in 0.1M KOH solution;

[0033] Figure 8is the LSV curve of Example 4 in 0.1M KOH solution;

[0034] Fig. 9 is the LSV curve of Example 5 in 0.1M KOH solution;

[0035] Fig.10 It is the SEM image of Comparative Example 2;

[0036] Fig.11 is the LSV curve of Comparative Example 2 in 0.1M KOH solution;

[0037] Fig.12 It is the SEM image of Comparative Example 3;

[0038] Fig.13 This is the LSV curve of Comparative Example 3 in 0.1 M KOH solution. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Example 1

[0041] Dissolve 2.4 g of dimethylimidazole in 60 mL of methanol and stir for 10 min to obtain a dimethylimidazole solution. Then take 2.23 g of Zn(NO 3 ) 2 6H 2 O and 0.11 gFeSO 4 7H 2 O was added to 60 mL of methanol and stirred for 10 min to obtain a mixed solution. Dimethylimidazole solution was added to the mixed solution to obtain a light yellow mixed solution, which was stirred at 25 °C for 24 h, washed with 80% ethanol and dried in vacuum at 60 °C for 12 h. 2 In an atmosphere of mixed gas with a volume ratio of 90:10, pyrolysis was carried out at 900 °C for 2 h and then cooled under Ar conditions to obtain ZIF8-Fe@CNTs-1.

[0042] SEM image of Example 1 of the present invention ( Figure 1 (b)) It can be seen that carbon nanotubes are grown in situ on the surface of carbon particles, which is obviously different from the morphology of ZIF8 carbon-based catalyst without adding iron source (prepared in Comparative Example 1; Figure 1 (a) TEM image ( Figure 2 ) and HR-TEM images ( Figure 3) showed that these in-situ grown carbon nanotubes formed a mutually cross-linked network structure on the particle surface, and the ZIF carbon particles were bridged by these in-situ grown carbon nanotubes. Figure 4 The HAADF-STEM image shows that single Fe atoms are densely distributed on the carbon nanoparticles and on the surface of carbon nanotubes. Figure 5 The prepared ZIF8-Fe@CNTs-1 catalyst 2 In saturated 0.1M KOH solution, the LSV curve at 1600rmp shows good oxygen reduction ORR activity, and the limiting current density is significantly higher than that of commercial Pt / C (20wt.%). In addition, the half-wave potential of the ZIF8-Fe@CNTs-1 catalyst is 0.906V, which is better than that of commercial Pt / C (0.853V). Figure 5 ). The high density of iron atoms distributed on the surface of the ZIF carbon matrix and the in-situ grown carbon nanotubes effectively increases the active sites and improves the intrinsic activity of the catalyst. In addition, the cross-linked structure of the ZIF carbon matrix and carbon nanotubes significantly improves the efficiency of material transport and charge transfer, thereby showing the characteristics of high current and high activity.

[0043] Example 2

[0044] Dissolve 2.4 g of dimethylimidazole in 60 mL of methanol and stir for 10 min to obtain a dimethylimidazole solution. Then take 2.23 g of Zn(NO 3 ) 2 6H 2 O and 0.14gFeSO 4 7H 2 O was added to 60 mL of methanol and stirred for 10 min to obtain a mixed solution. Dimethylimidazole solution was added to the mixed solution to obtain a light yellow mixed solution, which was stirred at 25 °C for 24 h, washed with 80% ethanol and dried in vacuum at 60 °C for 12 h. 2 In an atmosphere of mixed gas with a volume ratio of 90:10, pyrolysis was carried out at 900 °C for 2 h and cooling was carried out under Ar conditions to obtain ZIF8-Fe@CNTs-2.

[0045] Figure 6 The results show that the ZIF8-Fe@CNTs-2 catalyst prepared in this example 2 In saturated 0.1M KOH solution, the LSV curve at 1600 rpm showed good oxygen reduction ORR activity.

[0046] Example 3

[0047] Dissolve 2.4 g of dimethylimidazole in 60 mL of methanol and stir for 10 min to obtain a dimethylimidazole solution. Then take 2.23 g of Zn(NO 3 )2 6H 2 O and 0.22gFeSO 4 7H 2 O was added to 60 mL of methanol and stirred for 10 min to obtain a mixed solution. Dimethylimidazole solution was added to the mixed solution to obtain a light yellow mixed solution, which was stirred at 25 °C for 24 h, washed with 80% ethanol and dried in vacuum at 60 °C for 12 h. 2 In an atmosphere of mixed gas with a volume ratio of 90:10, pyrolysis was carried out at 900 °C for 2 h and then cooled under Ar conditions to obtain ZIF8-Fe@CNTs-3.

[0048] Figure 7 The prepared ZIF8-Fe@CNTs-3 catalyst was 2 In saturated 0.1 M KOH solution, the LSV curve at 1600 rpm showed good oxygen reduction ORR activity.

[0049] Example 4

[0050] Dissolve 2.4 g of dimethylimidazole in 60 mL of methanol and stir for 10 min to obtain a dimethylimidazole solution. Then take 2.23 g of Zn(NO 3 ) 2 6H 2 O and 0.22gFeSO 4 7H 2 O was added to 60 mL of methanol and stirred for 10 min to obtain a mixed solution. Dimethylimidazole solution was added to the mixed solution to obtain a light yellow mixed solution, which was stirred at 25 °C for 24 h, washed with 80% ethanol and dried in vacuum at 60 °C for 12 h. 2 In an atmosphere of mixed gas with a volume ratio of 90:10, pyrolysis was carried out at 1000 °C for 2 h and cooling was carried out under Ar conditions to obtain ZIF8-Fe@CNTs-4.

[0051] Figure 8 The prepared ZIF8-Fe@CNTs-4 catalyst was 2 In saturated 0.1 M KOH solution, the LSV curve at 1600 rpm showed good oxygen reduction ORR activity.

[0052] Example 5

[0053] Dissolve 2.4 g of dimethylimidazole in 60 mL of methanol and stir for 10 min to obtain a dimethylimidazole solution. Then take 2.23 g of Zn(NO 3 ) 2 6H 2 O and 0.22gFeSO 4 7H2 O was added to 60 mL of methanol and stirred for 10 min to obtain a mixed solution. Dimethylimidazole solution was added to the mixed solution to obtain a light yellow mixed solution, which was stirred at 25 °C for 24 h, washed with 80% ethanol and dried in vacuum at 60 °C for 12 h. 2 In an atmosphere of mixed gas with a volume ratio of 90:10, pyrolysis was carried out at 900 °C for 3 h and then cooled under Ar conditions to obtain ZIF8-Fe@CNTs-5.

[0054] Fig. 9 The prepared ZIF8-Fe@CNTs-5 catalyst was 2 In saturated 0.1 M KOH solution, the LSV curve at 1600 rpm showed good oxygen reduction ORR activity.

[0055] Comparative Example 1

[0056] Dissolve 2.4 g of dimethylimidazole in 60 mL of methanol and stir for 10 min to obtain a dimethylimidazole solution. Then take 2.23 g of Zn(NO 3 ) 2 6H 2 O was added to 60 mL of methanol and stirred for 10 min to obtain a mixed solution. Dimethylimidazole solution was added to the mixed solution to obtain a milky white mixed solution, which was stirred at 25 °C for 24 h, washed with 80% ethanol and dried in vacuum at 60 °C for 12 h. 2 In the atmosphere of mixed gas, the volume ratio was 90:10, pyrolysis was carried out at 900℃ for 2h, and cooling was carried out under Ar condition to obtain ZIF8 (such as Figure 1 (as shown in (a)).

[0057] Comparative Example 2

[0058] Dissolve 2.4 g of dimethyl imidazole in 60 mL of deionized water and stir for 10 min to obtain a dimethyl imidazole solution. Then take 2.23 g of Zn(NO 3 ) 2 6H 2 O and 0.11 gFeSO 4 7H 2 O was added to 60 mL of deionized water and stirred for 10 min to obtain a mixed solution. Dimethylimidazole solution was added to the mixed solution to obtain a light yellow mixed solution, which was stirred at 25 °C for 24 h, washed with 80% ethanol and dried in vacuum at 60 °C for 12 h. 2 In an atmosphere of mixed gas with a volume ratio of 90:10, pyrolysis was carried out at 900 °C for 2 h and cooling was carried out under Ar conditions to obtain ZIF8-W.

[0059] Comparative Example 3

[0060] Dissolve 2.4 g of dimethylimidazole in 60 mL of methanol and stir for 10 min to obtain a dimethylimidazole solution. Then take 2.23 g of Zn(NO 3 ) 2 6H 2 O and 0.11 gFeSO 4 7H 2 O was added to 60 mL of methanol and stirred for 10 min to obtain a mixed solution. Dimethylimidazole solution was added to the mixed solution to obtain a light yellow mixed solution, which was stirred at 25 °C for 24 h, washed with 80% ethanol and vacuum dried at 60 °C for 12 h. Under Ar gas conditions, it was pyrolyzed at 900 °C for 2 h and cooled under Ar conditions to obtain ZIF8-Ar.

[0061] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a metal single-atom carbon-based catalyst for in-situ growth of carbon nanotubes, characterized in that: The steps include: (1) dissolving dimethylimidazole in methanol to obtain solution A; (2) dissolving a transition metal salt and a zincate in methanol to form a solution B; (3) The solution A and the solution B are mixed to obtain a precursor; (4) The precursor is heat treated at 900-1100° C. in an inert gas and H 2 mixed gas to obtain the metal single atom carbon-based catalyst for in-situ growth of carbon nanotubes.

2. The preparation method according to claim 1, characterized in that: The transition metal salt is at least one of nitrate, acetate, chloride or sulfate of cobalt, iron, manganese, nickel or molybdenum; Furthermore, the transition metal salt is at least one of ferrous sulfate heptahydrate, ferric chloride hexahydrate, ferric acetylacetonate, and ferric nitrate nonahydrate.

3. The preparation method according to claim 2, characterized in that: The transition metal salt is ferrous sulfate heptahydrate.

4. The preparation method according to claim 1, characterized in that: The molar ratio of zincate to transition metal salt is 20:1-3.

5. The preparation method according to claim 1, characterized in that: The reaction temperature of step (3) is 10-30°C.

6. The preparation method according to claim 1, characterized in that: In step (3), an ethanol-water mixed solution is also used for washing, and the ethanol concentration is 65% to 85%.

7. The preparation method according to claim 1, characterized in that: The heat treatment time in step (4) is 1 to 4 hours.

8. The preparation method according to claim 1, characterized in that: In step (4), the inert gas is Ar and / or N2; further, the volume ratio of the inert gas to H2 is 100:2-10.

9. A metal single-atom carbon-based catalyst for in-situ growth of carbon nanotubes, characterized in that: The catalyst is obtained by any preparation method according to claims 1 to 8.

10. Use of the catalyst obtained by any preparation method according to claims 1 to 8 or the catalyst according to claim 9 in the fields of electrocatalysis, fuel cells and metal-air batteries.